Porous high-temperature conductive film, preparation method and application thereof, and solid oxide fuel cell

By preparing a porous high-temperature conductive film on the cathode surface of the solid oxide fuel cell, and using a sintering aid to improve the conductivity and form a porous structure, the problem of insufficient conductivity of the cathode current collector in the prior art is solved, and the output power and performance of the stack are improved.

CN119650746APending Publication Date: 2025-03-18ANHUI ESTONE MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411871344.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The cathode current collector of the existing solid oxide fuel cells is insufficient in electrical conductivity, resulting in a decrease in the output power of the stack and a decrease in performance.

Method used

The porous high-temperature conductive film is prepared by fully mixing conductive powder, sintering aid, dispersant and organic solvent, adding glue and high-temperature treatment to produce a porous high-temperature conductive film. Scaling aids such as metals, composites that decompose metal salts and metal oxides help improve the conductivity of the material and form porous structures.

Benefits of technology

It effectively improves the conductivity of the current collector film, reduces production costs, and stabilizes the collection and transmission of electrons, improving the stack performance of solid oxide fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650746A_ABST
    Figure CN119650746A_ABST
Patent Text Reader

Abstract

The invention discloses a porous high-temperature conductive thin film, a preparation method and application thereof and a solid oxide fuel cell, and relates to the technical field of solid oxide fuel cells. A current collector thin film can be directly prepared on the surface of a cathode of the solid oxide fuel cell by selecting a proper sintering aid to be compounded with lanthanum strontium cobalt; the collector layer is generated in situ at high temperature, so that the production cost is effectively reduced, electrons can be stably collected and transmitted, and the stack performance of the solid oxide fuel cell is improved; meanwhile, the preparation method provided by the invention is simple in process and easy for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid oxide fuel cells, and in particular to a porous high-temperature conductive film and a preparation method and application thereof, and a solid oxide fuel cell. Background Art

[0002] Solid oxide fuel cell (SOFC) is a third-generation fuel cell. It is an all-solid-state chemical power generation device that directly converts the chemical energy stored in fuel and oxidant into electrical energy in an efficient and environmentally friendly manner at medium and high temperatures.

[0003] In a flat SOFC stack, multiple flat SOFC battery cells need to be stacked and connected in series to increase the output voltage and output power. Each flat SOFC battery cell is composed of an anode, a cathode, and an electrolyte. Two adjacent SOFC battery cells are connected by a connector. Specifically, the connector is connected to the anode of one battery cell and to the cathode of another battery cell. During the operation of the stack, the current generated by multiple battery cells needs to be converged and output to the external circuit. In order to increase the output power of the stack, the contact resistance of the stack must be reduced. Since the contact impedance between the cathode and the connector is large, the battery output power will be reduced and the performance will be reduced. Therefore, a contact layer with good conductivity is often prepared on the cathode surface to improve the current collection efficiency. At present, the air electrode current collector of solid oxide fuel cells on the market is mainly a composite material of lanthanum strontium cobalt (LSC) and precious metal silver. Silver has good conductivity, but it is expensive, and during the operation of the solid oxide fuel cell, silver will migrate and volatilize, resulting in a decrease in the performance of the stack.

[0004] CN117334943A discloses a solid oxide fuel cell and a method for preparing the same, and discloses the direct use of lanthanum strontium manganese oxide as a contact layer, ie, a current collector, of the solid oxide fuel cell. However, the conductivity of the current collector layer prepared by this method still needs to be improved. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a porous high-temperature conductive film. By adding a sintering aid, on the one hand, it can serve as a connecting bridge for the main material and effectively improve the conductive performance of the material; on the other hand, the sintering aid makes the material form a porous form after high-temperature sintering, which is beneficial to gas contact, thereby improving the overall performance of the solid oxide fuel cell.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] One of the purposes of the present invention is to provide a method for preparing a porous high-temperature conductive film, comprising the following steps:

[0008] (1) Fully mixing the conductive powder, sintering aid, dispersant and organic solvent, then adding glue and mixing evenly to obtain slurry;

[0009] (2) treating the slurry to obtain a green body;

[0010] (3) subjecting the green body to high temperature treatment to obtain a porous high temperature conductive film;

[0011] The sintering aid is at least one of a metal, a decomposable metal salt, a complex of a metal oxide and a decomposable metal salt, and a complex of a metal and a decomposable metal salt; the decomposable metal salt is at least one of a metal carbonate, a metal bicarbonate, a metal oxalate, a metal succinate, and a metal acetylacetonate; and the metal is at least one of manganese, cobalt, copper, and iron.

[0012] A second object of the present invention is to provide a porous high-temperature conductive film prepared by the aforementioned method for preparing the porous high-temperature conductive film.

[0013] A third object of the present invention is to provide the application of the aforementioned porous high-temperature conductive film in solid oxide fuel cells.

[0014] A fourth object of the present invention is to provide a solid oxide fuel cell, using the aforementioned porous high-temperature conductive film as the cathode (air electrode) current collector material.

[0015] The beneficial effects of the present invention are as follows: by selecting a suitable sintering aid and compounding it with a conductive powder, the present invention can directly prepare a current collector film on the cathode surface of a solid oxide fuel cell, and generate a current collector layer in situ at a high temperature, which not only effectively reduces the production cost, but also can stably collect and transmit electrons, improve the conductivity of the current collector film, and thus improve the stack performance of the solid oxide fuel cell; at the same time, the preparation method provided by the present invention is simple in process and easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a surface SEM image of the green body in Example 2 after sintering at 750°C;

[0017] Figure 2 This is a cross-sectional SEM image of the green body in Example 2 after sintering at 750°C. DETAILED DESCRIPTION

[0018] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0019] The present invention provides a method for preparing a porous high-temperature conductive film, comprising the following steps:

[0020] (1) Fully mixing the conductive powder, sintering aid, dispersant and organic solvent, then adding glue and mixing evenly to obtain slurry;

[0021] (2) treating the slurry to obtain a green body;

[0022] (3) The green body is subjected to high temperature treatment to obtain a porous high temperature conductive film.

[0023] The sintering aid is at least one of a metal, a decomposable metal salt, a complex of a metal oxide and a decomposable metal salt, and a complex of a metal and a decomposable metal salt; the decomposable metal salt is at least one of a metal carbonate, a metal bicarbonate, a metal oxalate, a metal succinate, and a metal acetylacetonate; and the metal is at least one of manganese, cobalt, copper, and iron.

[0024] In the present invention, the conductive powder is selected from at least one of lanthanum strontium manganese (LSM) powder, lanthanum strontium cobalt (LSC) powder and lanthanum strontium cobalt iron (LSCF) powder. The preparation methods of the LSM powder, LSC powder and LSCF powder can adopt the coprecipitation method, sol-gel method, hydrothermal method and the like known to those skilled in the art. Further preferably, the specific surface area of ​​the conductive powder is 0.1 to 1.79 m 2 / g, and the average particle size is 20-30 μm. As a preferred embodiment, the method for preparing the LSC powder is a high temperature sintering method to obtain (La 0.6 Sr 0.4 ) 0.95 CoO 3-δ , its specific surface area is 0.1~1.79m 2 / g, with an average particle size of 20 to 30 μm. Among them, lanthanum strontium manganese (LSM) is lanthanum manganate doped with strontium oxide; lanthanum strontium cobalt or LSC is lanthanum cobaltate doped with strontium oxide; lanthanum strontium cobalt iron or LSCF is lanthanum cobaltate co-doped with strontium oxide and iron oxide.

[0025] In the present invention, the sintering aid does not react with the solvent and is insoluble in the solvent, and can generate metal oxides under high temperature conditions. The metal oxide is selected from at least one of manganese oxide, cobalt oxide, copper oxide and iron oxide; the metal carbonate is selected from at least one of manganese carbonate, cobalt carbonate, copper carbonate and iron carbonate; the metal oxalate is selected from at least one of manganese oxalate, cobalt oxalate, copper oxalate and iron oxalate; the metal acetylacetonate is selected from at least one of copper acetylacetonate, iron acetylacetonate, manganese acetylacetonate and cobalt acetylacetonate.

[0026] Under preferred conditions, the sintering aid is a decomposable metal salt, a metal oxide and a complex of a decomposable metal salt. For example, the sintering aid can be at least one of manganese oxide / manganese carbonate, cobalt oxide / cobalt carbonate, copper oxide / copper carbonate, iron oxide / iron carbonate, manganese oxide / manganese acetylacetonate, cobalt oxide / cobalt acetylacetonate, copper oxide / copper acetylacetonate and iron oxide / iron acetylacetonate, manganese oxide / manganese oxalate, cobalt oxide / cobalt oxalate, copper oxide / copper oxalate, and iron oxide / iron oxalate.

[0027] According to the present invention, under preferred conditions, the particle size of the sintering aid is less than 8 μm.

[0028] In the present invention, the dispersant is triethanolamine.

[0029] In the present invention, the glue is composed of 15 wt% adhesive, 10.7 wt% thickener, 10 wt% plasticizer and 64.3 wt% organic solvent. Exemplarily, the present application adopts ball milling method to prepare the glue.

[0030] Furthermore, the adhesive is polyvinyl butyral, for example, B-72 polyvinyl butyral and B-76 polyvinyl butyral.

[0031] Furthermore, the thickener is polyethylene glycol 400.

[0032] Furthermore, the plasticizer is dibutyl phthalate. The plasticizer can reduce the viscosity of the resin and improve the flexibility and processing performance of the adhesive.

[0033] Furthermore, the organic solvent is at least one of ethanol and butanone.

[0034] In the present invention, the solid content of the slurry is 50-70wt%, wherein the content of LSC powder is 56-60wt%, the content of sintering aid is 2-8wt%, the content of dispersant is 1-2wt%, and the content of glue is 20-30wt%.

[0035] In order to ensure the uniformity of dispersion of each component in the slurry, the mixing process is carried out in a homogenizer.

[0036] In the present invention, the slurry processing method includes preparing a current collector film green body on the cathode surface of the solid oxide fuel cell by using a casting method, an electrostatic spinning method, a screen printing method or an electroplating method. The specific process of the casting method, the electrostatic spinning method, the screen printing method or the electroplating method can be known to those skilled in the art, and will not be described in detail in this application.

[0037] In the present invention, the temperature of the high temperature treatment is 600-900°C.

[0038] The present invention provides a porous high-temperature conductive film prepared by the above-mentioned method for preparing a porous high-temperature conductive film.

[0039] The present invention provides the use of the aforementioned porous high-temperature conductive film in a solid oxide fuel cell.

[0040] The present invention also provides a solid oxide fuel cell, using the aforementioned porous high-temperature conductive film as the air electrode current collector material.

[0041] The conductivity and area specific resistance (ASR) in the following examples were measured by a digital multimeter using a four-probe method at a measurement temperature of 750°C.

[0042] The LSC powder in the following examples is (La 0.6 Sr 0.4 ) 0.95 CoO 3-δ .

[0043] Comparative Example 1

[0044] S1. Add 18.5 g of polyvinyl butyral B-76, 2.5 g of polyvinyl butyral B-72, 15 g of polyethylene glycol 400, 14 g of dibutyl phthalate, 54 g of ethanol, and 36 g of butanone into a planetary ball mill, and mill at a speed of 250 r / min for 8 h. Filter and obtain glue.

[0045] S2. Weigh 50 g of LSC powder, 1 g of triethanolamine, 5.4 g of ethanol, and 3.6 g of butanone into a homogenizer and mix well. Then add 25 g of glue, mix well, filter, and vacuum degas to obtain a slurry with a solid content of 58.8 wt%.

[0046] S3, casting the slurry on the cathode surface, debinding at 60°C, to obtain a current collector film green body.

[0047] S4. Sinter the green body at 750° C. for 13 h to obtain a porous high-temperature conductive film.

[0048] Comparative Examples 2 to 5

[0049] The method of Comparative Example 1 is followed, except that LSC powders with different specific surface areas are used, as shown in Table 1.

[0050] The films prepared in Comparative Examples 1 to 5 were subjected to ASR and conductivity tests. The test results are shown in Table 1.

[0051] Table 1

[0052] <![CDATA[Specific surface area of LSC powder (m 2 / g)]]> <![CDATA[ASR(mΩ·cm 2 )]]> Conductivity (S / cm) Comparative Example 1 0.45 84 26.50 Comparative Example 2 0.10 92 22.92 Comparative Example 3 1.79 96 25.98 Comparative Example 4 0.05 160 18.24 Comparative Example 5 2.59 224 13.45

[0053] It can be seen from Table 1 that the specific surface area of ​​LSC powder directly affects the conductive properties of the film. The smaller the ASR, the greater the conductivity and the better the conductive properties. However, when the specific surface area of ​​LSC is less than 0.1 m 2 / g, further reducing the specific surface area of ​​LSC will lead to an increase in the area specific resistance of the obtained film and a decrease in the conductivity. Therefore, the specific surface area of ​​LSC is preferably 0.1 to 1.79 m 2 / g, more preferably 0.45m 2 / g of LSC powder.

[0054] Examples 1 to 3 and Comparative Example 6

[0055] The method of Comparative Example 1 is followed, except that copper acetylacetonate (average particle size of 5 μm) is added as a sintering aid when preparing the slurry. The solid content of the slurry is 62 wt %. The content of copper acetylacetonate is specifically shown in Table 2.

[0056] The films prepared in Examples 1 to 3 and Comparative Example 6 were subjected to ASR and conductivity tests. The test results are shown in Table 2.

[0057] Table 2

[0058] Copper acetylacetonate content (wt%) <![CDATA[ASR(mΩ·cm 2 )]]> Conductivity (S / cm) Comparative Example 1 0 84 26.50 Example 1 5 64 36.50 Example 2 2 75 28.24 Example 3 8 76 28.91 Comparative Example 6 10 92 22.21

[0059] It can be seen from Table 2 that the addition of copper acetylacetonate as a sintering aid can improve the conductivity of the film, but the amount of the sintering aid is not the more the better. When the amount of the sintering aid is too large (such as 10wt%), the conductivity of the film decreases. Therefore, it is necessary to control the amount of the sintering aid within the range of 2 to 8wt%.

[0060] like Figure 1 He Ru Figure 2 As shown, the film green body naturally generates a porous morphology after high-temperature sintering, which allows the gas to fully contact and quickly penetrate, laying the foundation for the application of this material in the air electrode current collector of solid oxide fuel cells.

[0061] Examples 4 to 6 and Comparative Example 7

[0062] The method of Example 1 was followed, except that the particle size of the sintering aid was changed, as shown in Table 3.

[0063] The films prepared in Examples 4 to 6 and Comparative Example 7 were subjected to ASR and conductivity tests. The test results are shown in Table 3.

[0064] Table 3

[0065]

[0066]

[0067] It can be seen from Table 3 that the particle size of the sintering aid is an important factor affecting the performance of the current collector layer. The smaller the particle size of the sintering aid, the more conducive it is to charge transfer, especially when the particle size of the sintering aid reaches the nanometer level, its performance is significantly improved, but when its particle size exceeds 8μm, the particle sizes of the sintering aid and the main material are both micrometer-level, and the charge transfer effect is reduced, which will not only fail to improve the performance of the current collector layer film, but will deteriorate the performance of the current collector layer film, resulting in an increase in the area specific resistance of the current collector layer film and a decrease in conductivity.

[0068] Examples 7 to 9 and Comparative Example 8

[0069] The method of Example 1 is followed, except that the type of sintering aid is changed, as shown in Table 4.

[0070] The films prepared in Examples 7 to 9 and Comparative Example 8 were subjected to ASR and conductivity tests. The test results are shown in Table 4.

[0071] Table 4

[0072] Types of burning aids <![CDATA[ASR(mΩ·cm 2 )]]> Conductivity (S / cm) Example 1 Copper acetylacetonate 64 36.50 Example 7 Basic copper carbonate 65 35.25 Example 8 Manganese carbonate 73 29.08 Example 9 copper 75 28.69 Comparative Example 8 Copper Oxide 82 26.73

[0073] It can be seen from Table 4 that compared with metal oxides, when the sintering aid is a decomposable metal salt or pure metal, it has a positive effect on the performance of the current collecting layer. The main reason is that under high temperature environment, the sintering aid reacts to different degrees, effectively changes the internal pore environment of the current collecting layer, improves the gas dynamics, and thus improves the performance of the current collecting material.

[0074] Embodiments 10 to 13

[0075] The method of Example 1 is followed, except that a composite of metal oxide and decomposable metal salt is used as a sintering aid, the dosage ratio of metal oxide to decomposable metal salt is changed, and the total dosage of the sintering aid is 5 wt %, as shown in Table 5.

[0076] The films prepared in Examples 10-13 were subjected to ASR and conductivity tests. The test results are shown in Table 5.

[0077] Table 5

[0078]

[0079] It can be seen from Table 5 that, compared with a single decomposable metal salt, when the sintering aid is a complex of a metal oxide and a decomposable metal salt, and the weight ratio of the metal oxide to the decomposable metal salt is (2-3):(2-3), the area specific resistance of the prepared film is lower and the conductivity is greater.

[0080] Embodiments 14 to 18

[0081] The method of Example 10 is followed, except that the types of metal oxide and decomposable metal salt are adjusted, and the amounts of fixed metal oxide and decomposable metal salt are 2% and 3%, respectively, as shown in Table 6.

[0082] The films prepared in Examples 14-18 were subjected to ASR and conductivity tests. The test results are shown in Table 6.

[0083] Table 6

[0084]

[0085] It can be seen from Table 6 that, compared with the pure main material, when the sintering aid is a composite of 2 wt % metal oxide and 3 wt % decomposable metal salt, the performance of the current collecting material is improved.

[0086] Examples 19-22

[0087] The method of Example 1 is followed, except that a complex of metal and decomposable metal salt is used as a sintering aid, the dosage ratio of metal to decomposable metal salt is changed, and the total dosage of the sintering aid is 5 wt %, as shown in Table 7.

[0088] The films prepared in Examples 19-22 were subjected to ASR and conductivity tests. The test results are shown in Table 7.

[0089] Table 7

[0090]

[0091] It can be seen from Table 7 that, compared with using only metal or decomposable metal salt as a sintering aid, when the sintering aid is a complex of metal and decomposable metal salt, the performance of the current collecting material can be improved.

[0092] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a porous high-temperature conductive film, characterized in that: The preparation method comprises the following steps: (1) Fully mixing the conductive powder, sintering aid, dispersant and organic solvent, then adding glue and mixing evenly to obtain slurry; (2) treating the slurry to obtain a green body; (3) subjecting the green body to high temperature treatment to obtain a porous high temperature conductive film; The sintering aid is at least one of a metal, a decomposable metal salt, a complex of a metal oxide and a decomposable metal salt, and a complex of a metal and a decomposable metal salt; The decomposable metal salt is selected from at least one of metal carbonates, metal bicarbonates, metal oxalates, metal succinates and metal acetylacetonates; The metal is selected from at least one of manganese, cobalt, copper and iron.

2. The method for preparing a porous high-temperature conductive film according to claim 1, characterized in that: The conductive powder is selected from at least one of lanthanum strontium manganese, lanthanum strontium cobalt and lanthanum strontium cobalt iron; Preferably, the specific surface area of ​​the conductive powder is 0.1 to 1.79 m 2 / g, and the average particle size is 20 to 30 μm.

3. The method for preparing a porous high temperature conductive film according to claim 1, characterized in that: The sintering aid is one of a decomposable metal salt, a metal oxide, a decomposable metal salt, and a complex of a metal and a decomposable metal salt; Preferably, the particle size of the sintering aid is less than 8 μm.

4. The method for preparing a porous high temperature conductive film according to claim 1, characterized in that: The dispersant is triethanolamine; Preferably, the organic solvent is at least one of ethanol and butanone.

5. The method for preparing a porous high temperature conductive film according to claim 1, characterized in that: The glue is composed of an adhesive, a thickener, a plasticizer and an organic solvent; Preferably, the adhesive is polyvinyl butyral; Preferably, the thickener is polyethylene glycol 400; Preferably, the plasticizer is dibutyl phthalate; Preferably, the organic solvent is at least one of ethanol and butanone.

6. The method for preparing a porous high temperature conductive film according to claim 1, characterized in that: The solid content of the slurry is 50-70wt%; Preferably, the content of the sintering aid in the slurry is 2-8 wt %.

7. The method for preparing a porous high temperature conductive film according to claim 1, characterized in that: The slurry is processed by a casting method, an electrostatic spinning method, a screen printing method or an electroplating method; Preferably, the temperature of the high temperature treatment is 600-900°C.

8. A porous high-temperature conductive film prepared by the method for preparing a porous high-temperature conductive film according to any one of claims 1 to 7.

9. Use of the porous high-temperature conductive film according to claim 8 in solid oxide fuel cells.

10. A solid oxide fuel cell, using the porous high temperature conductive film according to claim 8 as a cathode current collector.

Citation Information

Patent Citations

  • Solid oxide fuel cell and preparation method thereof

    CN117334943A